Comparison of Different Machine Models Based on Contrast-Enhanced Computed Tomography Radiomic Features to Differentiate High From Low Grade Clear Cell Renal Cell Carcinomas - Pei, Xu; Wang, Ping; Ren, Jia-Liang; Yin, Xiao-Ping; Ma, Lu-Yao; Wang, Yun; Ma, Xi; Gao, Bu-Lang (Frontiers in Oncology, 2021)
Purpose: This study was to investigate the role of different radiomics models with enhanced computed tomography (CT) scan in differentiating low from high grade renal clear cell carcinomas. Materials and methods: CT data of 190 cases with pathologically confirmed renal cell carcinomas were collected and divided into the training set and testing set according to different time periods, with 122 cases in the training set and 68 cases in the testing set. The region of interest (ROI) was delineated layer by layer. Results: A total of 402 radiomics features were extracted for analysis. Six of the radiomic parameters were deemed very valuable by univariate analysis, rank sum test, LASSO cross validation and correlation analysis. From these six features, multivariate logistic regression model, support vector machine (SVM), and decision tree model were established for analysis. The performance of each model was evaluated by AUC value on the ROC curve and decision curve analysis (DCA). Among the three prediction models, the SVM model showed a high predictive efficiency. The AUC values of the training set and the testing set were 0.84 and 0.83, respectively, which were significantly higher than those of the decision tree model and the multivariate logistic regression model. The DCA curve analysis revealed a better predictive performance in the SVM model that possessed the highest degree of coincidence. Conclusion: Radiomics analysis with the 3D data can better reflect the tumor heterogeneity, with using the SVM radiomics model being has highly efficiencyt in discriminating high- and low-grade clear cell renal cell carcinomas.